2023
DOI: 10.3892/ol.2023.13661
|View full text |Cite
|
Sign up to set email alerts
|

Worst pattern of invasion and other histopathological features in oral cancer as determinants of prognosis and survival rate: A retrospective cohort analysis

Abstract: Oral cavity squamous cell carcinoma (OCSCC) is a well-recognized malignancy of the head and neck. Studies on patients with early-stage oral cancer have shown that they develop locally recurring and/or regional lymph node metastasis, which results in disease-associated mortality. Thus, early-stage oral cancer does not always present good prognoses. The present study aimed to determine the efficacy of using worst pattern of invasion (WPOI) and other histopathological features, such as prognostic factors in OCSCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…These variables included age, sex, race, Charlson-Deyo comorbidity score, median census-tract income, insurance status, tumor size, pathologic N status, presence of lymphovascular invasion, extracapsular extension, adjuvant chemotherapy and/or radiation use, neck dissection surgery, and surgical margin positivity. 3,18 Analysis for the overall cohort also included adjustment on primary oral cavity subsite. A case complete approach was used to address any potential missing data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variables included age, sex, race, Charlson-Deyo comorbidity score, median census-tract income, insurance status, tumor size, pathologic N status, presence of lymphovascular invasion, extracapsular extension, adjuvant chemotherapy and/or radiation use, neck dissection surgery, and surgical margin positivity. 3,18 Analysis for the overall cohort also included adjustment on primary oral cavity subsite. A case complete approach was used to address any potential missing data.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable‐adjusted Cox proportional hazards analyses were performed to control for variables determined a priori that would most likely act as confounders. These variables included age, sex, race, Charlson–Deyo comorbidity score, median census‐tract income, insurance status, tumor size, pathologic N status, presence of lymphovascular invasion, extracapsular extension, adjuvant chemotherapy and/or radiation use, neck dissection surgery, and surgical margin positivity 3,18 . Analysis for the overall cohort also included adjustment on primary oral cavity subsite.…”
Section: Methodsmentioning
confidence: 99%
“…DOI represents one of the most important prognostic parameters for the appearance of neck metastases in OSCC. In numerous analyses, DOI is an independent prognostic factor that is associated with tumor size, especially in patients with T1-T2 stage 22 . A study that included 161 patients with OSCC and clinical N0 findings in the neck indicated a correlation between DOI andmetastases in the regional lymph nodes of the neck 23 .…”
Section: Discussionmentioning
confidence: 99%
“…DOI predstavlja jedan od važnijih prognostičkih parametara pojave metastaza na vratu kod OSCC-a. U mnogobrojnim analizama DOI predstavlja nezavisni prognostički faktor koji je povezan sa veličinom tumora, naročito kod pacijenata sa T1-T2 stadijumom 22 . Istraživanje koje je obuhvatilo 161 pacijenata sa OPK-om i kliničkim N0 nalazom na vratu ukazalo je na postojanje korelacije između DOI i pojave metastaza u regionalnim limfnim nodusima vrata 23 .…”
Section: Diskusijaunclassified